Worldwide mobilizations : class struggles and urban commoning - Kalb, Don, 1959-; Mollona, Massimiliano, 1969- (Dislocations, 2018)
The past decades have seen significant urban insurrections worldwide, and this volume analyzes some of them from an anthropological perspective; it argues that transformations of urban class relationships must be approached in a way that is both globally informed and deeply embedded in local and popular histories, and contends that every case of urban mobilization should be understood against its precise context in the global capitalist transformation. The book examines cases of mobilization across the globe, and employs a Marxian class framework, open to the diverse and multi-scalar dynamics of urban politics, especially struggles for spatial justice.